Frequency and Outcome of Graft versus Host Disease after Stem Cell Transplantation: A Six-Year Experience from a Tertiary Care Center in Pakistan. (26th June 2013) - Ali, Natasha; Adil, Salman Naseem; Shaikh, Mohammad Usman; Masood, Nehal
Abstract : Objective . The objective of this study was to evaluate the frequency and outcome of graft versus host disease after stem cell transplantation for various haematological disorders in Pakistan. Materials and Methods . Pretransplant workup of the patient and donor was performed. Mobilization was done with G-CSF 300  μ g twice daily for five day. Standard GvHD prophylaxis was done with methotrexate 15 mg/m 2 on day +1 followed by 10 mg/m 2 on days +3 and +6 and cyclosporine. Grading was done according to the Glucksberg classification. Results . A total of 153 transplants were done from April 2004 to December 2011. Out of these were allogeneic transplants. There were females and males. The overall frequency of any degree of graft versus host disease was 34%. Acute GvHD was present in patients while had chronic GvHD. Grade II GvHD was present in patients while grade III and IV GvHD was seen in patients each. Acute myeloid leukemia and chronic myeloid leukemia were most commonly associated with GvHD. The mortality in acute and chronic GvHD was 8.8% and 12% respectively. Conclusion . The frequency of graft versus host disease in this study was 34% which is lower compared to international literature. The decreased incidence can be attributed to reduced diversity of histocompatibility antigens in our population.